FSErasing: Improving Face Recognition with Data Augmentation Using Face Parsing - Hiroya Kawai; Koichi Ito; Hwann-Tzong Chen; Takafumi Aoki (IET Biometrics)
We propose original semantic labels for detailed face parsing to improve the accuracy of face recognition by focusing on parts in a face. The part labels used in conventional face parsing are defined based on biological features, and thus, one label is given to a large region, such as skin. Our semantic labels are defined by separating parts with large areas based on the structure of the face and considering the left and right sides for all parts to consider head pose changes, occlusion, and other factors. By utilizing the capability of assigning detailed part labels to face images, we propose a novel data augmentation method based on detailed face parsing called Face Semantic Erasing (FSErasing) to improve the performance of face recognition. FSErasing is to randomly mask a part of the face image based on the detailed part labels, and therefore, we can apply erasing-type data augmentation to the face image that considers the characteristics of the face. Through experiments using public face image datasets, we demonstrate that FSErasing is effective for improving the performance of face recognition and face attribute estimation. In face recognition, adding FSErasing in training ResNet-34 with Softmax using CelebA improves the average accuracy by 0.354 points and the average equal error rate (EER) by 0.312 points, and with ArcFace, the average accuracy and EER improve by 0.752 and 0.802 points, respectively. ResNet-50 with Softmax using CASIA-WebFace improves the average accuracy by 0.442 points and the average EER by 0.452 points, and with ArcFace, the average accuracy and EER improve by 0.228 points and 0.500 points, respectively. In face attribute estimation, adding FSErasing as a data augmentation method in training with CelebA improves the estimation accuracy by 0.54 points. We also apply our detailed face parsing model to visualize face recognition models and demonstrate its higher explainability than general visualization methods.